2022
DOI: 10.1111/jocn.16328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of decision aids on breast reconstruction: A systematic review and meta‐analysis of randomised controlled trials

Abstract: Aims and Objectives:To systematically evaluate the effects of decision aids for women facing breast reconstruction decision on decision conflict, decision regret, knowledge, satisfaction, anxiety and depression.Background: Breast reconstruction decision is not good or bad and should be guided by clinical evidence and patient preferences. Decision aids can increase the patient's decision-making enthusiasm and ability, improve the quality of decision and promote shared decision-making between patients and medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 70 publications
3
8
0
Order By: Relevance
“…In line with the results of a previous meta-analysis [26], web-based decision aids reduced decision conflict. Decision conflicts were as high as 45.68 (SD 23.40) among women who were newly diagnosed with early-stage BC in China [47].…”
Section: Effectiveness Of Web-based Decision Aidssupporting
confidence: 84%
See 1 more Smart Citation
“…In line with the results of a previous meta-analysis [26], web-based decision aids reduced decision conflict. Decision conflicts were as high as 45.68 (SD 23.40) among women who were newly diagnosed with early-stage BC in China [47].…”
Section: Effectiveness Of Web-based Decision Aidssupporting
confidence: 84%
“…This review also did not include the effects of decision aids on outcome indicators such as psychologically relevant outcomes. Yang et al [ 26 ] conducted a meta-analysis exploring the effects of decision aids on decision-making in PMBR; however, the authors did not compare whether different forms of decision aids would have different effects. Zhao et al [ 27 ] conducted a scoping review with the aim of reviewing, comparing, and discussing the current incorporation of the adverse effects of BC treatments into decision aids and examined how web-based decision aids personalized BC treatment decision-making tools in patient–health care provider communication, clinician decision-making processes, and shared decision-making, as yet unassessed patient outcomes (eg, knowledge and anxiety).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, DAs favorably affect clinical outcomes by enhancing risk perception accuracy (Stacey, Légaré, Lewis, Barry, et al, 2017; van Weert et al, 2016) and adherence (Nathan et al, 2016; Paskins et al, 2020; Song et al, 2022; Torres Roldan et al, 2021). The findings of some studies indicated that the implementation of DA interventions resulted in significant improvements in patient satisfaction (Berlin et al, 2019; Collée et al, 2020; Grüne et al, 2021; Staszewska et al, 2017; Tong et al, 2021; Wieringa et al, 2019; Yang et al, 2022), health (Grüne et al, 2021; Staszewska et al, 2017), and emotional (Staszewska et al, 2017; Violette et al, 2015; Vromans, Tenfelde, et al, 2019) outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…SRs include various medical disciplines such as oncology (Martínez‐Alonso et al, 2017), chronic illness management (Wieringa et al, 2019), surgical interventions (Pacheco‐Brousseau et al, 2021), obstetrics and gynecology (Whybrow et al, 2022), and geriatric care (van Weert et al, 2016). Across all domains, the literature consistently highlights favorable results for patients, including improved knowledge (O'Connor et al, 2007), increased participation in decision‐making (Scalia et al, 2019), reduced decision conflict (Yang et al, 2022), and improved accuracy of risk perception in preventative treatments (Stacey, Légaré, Lewis, Barry, et al, 2017). Healthcare provider‐related outcomes include enhanced satisfaction (Yung et al, 2021), increased consultation length (Coronado‐Vázquez et al, 2019), and reduced decision conflict (Dobler et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There is a clear need to improve communication between healthcare professionals and breast cancer patients, this should involve both improved training for healthcare professionals and better implementation of tools to support decision making. Breast cancer decision aids are available, and evidence suggests they can improve decision related outcomes for patients by reducing decisional conflict and increasing knowledge and satisfaction [ 24 ]. The barriers and facilitators to embedding the use of decision aids in patient care need to be better understood to support their successful implementation.…”
Section: Discussionmentioning
confidence: 99%